Introduction: Special issue celebrating the life and work of Larry E. Smith. Issue 3 (8th October 2018) - Bolton, Kingsley; Davis, Daniel R.
Abstract: This brief introduction provides a short biography of Professor Larry Eugene Smith, who passed away in December 2014. The introduction also discusses the contents of this special issue, which pays tribute to the life and work of Professor Smith. All of the sixteen substantive articles have been contributed by Larry's friends and colleagues from the US as well as from many other societies worldwide. Larry's personal and professional reach was truly international in scope, as this collection of articles bears direct witness.